Exit, Voice, and the Role of Corporate Directors: Evidence from Acquisition Performance - William O. Brown Jr.; Michael T. Maloney (Claremont McKenna College, Department of Economics, 1999)
This study examines the characteristics of corporate boards for 82 companies that attempted 106 acquisitions during the 1980s. We find that poor performance is more likely to occur in firms that have recently experienced higher turnover of outside and lower turnover of inside directors. Companies with smaller boards, more reputable members, and larger equity holdings also outperform their counterparts. Our results do not suggest that more outside directors lead to improved performance but that outsiders often resign from the board instead of challenging managerial shirking. We conclude that choosing directors for whom board exit is costly will better reduce agency costs.
Keywords: 330